Rethinking Sextortion in Malaysia: Lessons from Indonesia on Legal Reform and Victim Protection - Mazlifah Mansoor; Yasmirah Mandasari Saragih (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Sextortion consists of elements of sexual exploitation and corruption. It occurs when an individual in a position of authority demands sexual favours in exchange for the performance or non-performance of an official duty. In Malaysia, sextortion remains unrecognised as a distinct criminal offence and prosecuted under fragmented statutory provisions such as the Malaysian Anti-Corruption Commission Act 2009 (Act 694) or the Penal Code (Act 574). This article adopts a doctrinal legal methodology to examine the adequacy of Malaysia’s current legal framework. It draws comparative insights from Indonesia, where sexual gratification has been interpreted as a form of corrupt benefit under the Law No. 31 of 1999 on the Eradication of Corruption Crimes and the Law No. 12 of 2022 on Sexual Violence Crimes (TPKS). The study integrates international and regional literature on sextortion and victim psychology to propose comprehensive reform in Malaysia. The findings suggest that: (1) sextortion should be explicitly included within the definition of “gratification” in Section 3 of the Malaysian Anti-Corruption Commission Act 2009; (2) trauma-informed and victim-centred investigation procedures should be embedded into enforcement practice; and (3) cross-agency coordination between the Malaysian Anti-Corruption Commission (MACC), police, and Anti-Sexual Harassment Tribunal is essential. Comparative lessons from Indonesia demonstrate that clear statutory recognition of sexual gratification as corruption enhances accountability and strengthens victim protection in the digital age.